Experimental study of concrete damage under high hydrostatic pressure - Cui, J.; Hao, Hong; Shi, Y.; Li, X.; Du, K. (Pergamon, 2017)
The objective of this study is to characterize the damage evolution behavior of concrete under hydrostatic pressures varying from 30 MPa to 500 MPa for better understanding the concrete material properties at complex stress states. A series of uniaxial tests were carried out to evaluate the damage degree of concrete after hydrostatic tests and a number of microscopic observations were also provided to allow visualizing the changes of microstructures of the specimen after and before hydrostatic tests. The effect of stress path on compressive meridian and tensile meridian of concrete was also studied. Experimental results indicate that concrete suffers obvious damage if the applied hydrostatic pressure is higher than the uniaxial compressive strength of concrete specimen. The strength and Young's modulus of concrete decrease significantly after hydrostatic tests and the aggregate-mortar interfacial transition zone (ITZ) is the most obvious damage region. The stress path has insignificant effects on ultimate strength envelopes. But if the stress path involves a high hydrostatic pressure that damages the concrete specimens upon unloading, the strength envelope “shrinks” because of the damage to concrete due to high hydrostatic pressure.